A multiple risk factor perspective on the prediction of literacy acquisition and learning difficulties for Spanish children ages 4-6 and 5-7 - Giménez-de-la-Peña, Almudena; Luque-Vilaseca, Juan Luis; Ortiz-García, Andrés; Cobo, Amparo; López-Zamora, Miguel; Sánchez, Auxiliadora; López-Pérez, Javier (My University, 2019)
The goal or this research is to identify the tasks with the highest predictive power yusing a Multidimensional Longitudinal Approach within a prevention-oriented RtI model. The assessment of genetic family risk, early linguistic and cognitive skills on Spanish literacy acquisition and learning difficulties was carried on in two cohorts of 850 4-7 and 3-6 year-old-children. Results show that phonological skills are predictive from the beginning of the assessment, reading abilities take relevance later on, and then other components as aritmetics or motor skills take place.
Keywords: Dislexia; Dyslexia; Risk; Early detection; Prediction